The Relationship between Leg Muscle Strength and Back Muscle Flexibility on Shooting Results of Futsal Athletes - Amir Supriadi (Jurnal Pendidikan Jasmani (JPJ), 2022)
This study aims to determine the relationship between leg muscle strength and back muscle flexibility to shooting Academy Futsal Athletes in 2022. This research was carried out in the Futsal Academy Bangsal 13 Fc field. The population in this study were all athletes of the soccer school ward 13 as many as 30 people. Sampling was carried out using purposive random sampling, with 10 people being the sample. Data analysis techniques used to test the hypothesis are normality test, linearity test, and correlation test. From the results of the first hypothesis correlation test, a significance value of 0.043 <0.05 was obtained, so there was a significant relationship between leg muscle strength and the results of shooting the ball. The results of the second hypothesis test have a significance value of 0.032 < 0.05, so there is a significant relationship between Back Muscle Flexibility and the results of shooting the ball. Based on the multiple correlation test in the summary model table, it is known that the magnitude of the relationship between Leg Muscle Strength and Back Muscle Flexibility (simultaneously) on the ball shooting results calculated by the correlation coefficient is 0.488, this indicates a moderate effect. Meanwhile, the simultaneous contribution or contribution of the Leg Muscle Strength with Back Muscle Flexibility is 23.8%, while 76.2% is determined by other variables.